Trends and determinants of underweight and overweight/obesity among urban Ethiopian women from 2000 to 2016 - Kedir Y. Ahmed; Solomon Abrha; Andrew Page; Amit Arora; Solomon Shiferaw; Fentaw Tadese; Canaan Negash Seifu; Tebikew Yeneabat; Emana Alemu; Delelegn Yilma Gebremichael; Abdulaziz Seiko; Felix Akpojene Ogbo (BMC, 2020)
Abstract Background Nutritional, epidemiological and demographic transitions have been associated with the emergence of the double burden of malnutrition globally. In Ethiopia, there has been no nationally representative investigation of trends and determinants of both underweight and overweight/obesity among urban women. This study examined the trends and determinants of underweight and overweight/obesity in urban Ethiopian women from 2000 to 2016. Methods Trends in the prevalence of underweight and overweight/obesity were investigated based on a series of the Ethiopia Demographic and Health Survey (EDHS) data for the years 2000 (n = 2559), 2005 (n = 1112), 2011 (n = 3569), and 2016 (n = 3106). Multivariable multinomial logistic regression was used to investigate the association between socioeconomic, demographic, behavioural, and community-level factors with underweight and overweight/obesity. Results The prevalence of underweight in urban Ethiopian women reduced significantly from 23.2% (95% confidence interval [CI]: 20.3, 26.3%) in 2000 to 14.8% (95% CI: 13.1, 16.7%) in 2016, while overweight/obesity increased significantly from 10.9% (95% CI: 9.1, 13.0%) in 2000 to 21.4% (95% CI: 18.2, 25.1%) in 2016. Urban women from rich households and those who had never married were less likely to be underweight. Urban women who were from wealthy households and those who attained at least secondary education were more likely to be overweight/obese. Women who were informally employed and listened to the radio were less likely to be overweight/obese compared to those who were unemployed and did not listen to the radio, respectively. Conclusion The prevalence of overweight/obesity increased from 2000 to 2016, with a concurrent reduction in the prevalence of underweight. Interventions aiming to reduce overweight and obesity should target urban women with higher education, those who resided in wealthier households and those who watched the television.